Formulasi Formulasi Dan Uji Stabilitas Sediaan Sabun Padat Minyak Atsiri Daun Serai (Cymbopogon citratus (DC.) Stapf) Kombinasi Ektrak Daun Daun Pandan (Pandanus amaryllifolius) - TITI PUDJI RAHAYU; Tri Rejeki Kartika Sari (Universitas Muhammadiyah Klaten, 2020)
Triclocarban is an antibacterial agent that is usually found in solid soaps and can cause resistance if used long term. Lemongrass (Cymbopogon citratus (DC) Stapf) is a natural ingredient that contains triclocarban. The purpose of this study was to make a formulation and determining whether the solid soap formulation of lemongrass essential oil (Cymbopogon citratus (DC) Stapf) combination of Pandan leaves ethanol extract (Pandanus amaryllioflius) as the stability test requirements. The method in this research used water content test, free fatty acid content test, and pH level test. From the results of this research, the water content test showed that the lowest water content was formula 3 at 5.8%, while the highest water content was in the first formulation, which was 10.45%. Formula 2 moisture content of 7.1%. The results of the free fatty acid content test showed formula 1, 2 and 3, namely formula 1 0.246, formula 2 0.168 and formula 3 0.123 with the addition of 0.5 grams of lemongrass oil formula 1, formula 2 as much as 0.75 grams and formula 3 as much as 1 gram. The addition of sucrose formulas 1, 2 and 3 every 15.0 grams. The addition of ethanol formulation 1 was 26.3 grams, formulation 2 was 26.05 grams and formulation 3 was 25.8 grams. While the results of the pH level test show that the pH value of formula 1 pH 9.8, formula 2 pH 9.3 and formula 3 pH 9.2 meet the standard pH requirements for soap preparations based on SNI standards is soap 9-11.